TEACHERS' TRAINING FOR SOCIAL AND EDUCATIONAL ACTIVITY IN CONDITIONS OF MOUNTAIN AREA PRIMARY SCHOOL - Leonida Pesotskaya (Vasyl Stefanyk Precarpathian National University, 2015)
The article reveals the question of using of the method of coaching in preparation of the students to the managerial activity in the sphere of preschool education in mountain areas. The necessity of preparation under the modern conditions of social-economic development of mountain areas has been proved. The content of the article generalizes basic contradictions between the necessity and reality. The definition of the main points of the research has been given. The attention is accentuated on the basic principles of management and on the notion "coaching" in the process of management of preschool education in mountain area. Coaching includes partnership, potential revealing, effectiveness. Methodology of coaching is based on the principle that the person naturally is sufficiently talented and owns great potential, which isn't realized fully. An important condition of this approach is valuable, respectful attitude of the participants of polylogue to one another. Basic theoretical regulations of the coaching approach have been determined. In the context of selection of teching technologies on the basis of coaching approach, the method "reflexive team" has been briefly revealed. It is determined that coaching is a style of management, transformed culture: if the authoritarian style is substituted into coaching, then the hierarchy changes from the support of blaming and ridiculing to the objective evaluation, all-hands activity changes to strategic planning. Coaching approach will allow optimizing the structure of economic activity of a separate preschool educational establishment. The attention is accentuated at the fact, that using coaching with the students at the lessons as a style of management of preschool education, will let future managers of preschool educational establishments to form the skills of behavior in critical situations of mountain area, to enrich their activity with the new means of performing, to develop professional flexibility and mobility, to learn clearly to determine the goals and priorities of activity of preschool educational establishment.